Pengembangan Kewirausahaan Ramah Lingkungan melalui Pelatihan Produk Pembersih Cemara di Pesantren Daarus Sunnah Rangkasbitung: Pengabdian - Panji Putranto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service activity aims to improve the entrepreneurial skills of students through training in making environmentally friendly cleaning products from pine plants. The Daarus Sunnah Rangkasbitung Islamic Boarding School was chosen as the location for the activity because it has local potential that can be utilized productively and a strong spirit of independence among students. The implementation method of the activity includes socialization, technical training in making natural cleaners, introduction to the concept of entrepreneurship, and production assistance. The results of the activity showed that the participants were able to understand the product manufacturing process, identify its economic benefits, and show interest in developing a business independently. This activity makes a real contribution to strengthening the entrepreneurial spirit and sustainable utilization of local resources. Therefore, this training is recommended to be implemented sustainably and developed into a boarding school business unit managed by students.